2012
DOI: 10.1111/j.1551-2916.2012.05452.x
|View full text |Cite
|
Sign up to set email alerts
|

Accommodation of Excess Oxygen in Group II Monoxides

Abstract: Atomic scale simulations are used to predict how excess oxygen is accommodated across the group II monoxides. In all cases, the preference is to form a peroxide ion centered at an oxygen site, rather than a single oxygen species, although the peroxide ionic orientation changes from <100> to <110> to <111> with increasing host cation radius. The enthalpy for accommodation of excess oxygen in BaO is strongly negative, whereas in SrO it is only slightly negative and in CaO and MgO the energy is positive. Interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 28 publications
4
33
0
Order By: Relevance
“…Previous thermodynamic analysis of Sr-oxide phases have shown that under these conditions SrO 2 is stable. 65 At higher temperatures (>527°C) 65 18 Figure S8 (a).…”
Section: Near-surface Atomic Structure and Composition By Stem And Edmentioning
confidence: 97%
“…Previous thermodynamic analysis of Sr-oxide phases have shown that under these conditions SrO 2 is stable. 65 At higher temperatures (>527°C) 65 18 Figure S8 (a).…”
Section: Near-surface Atomic Structure and Composition By Stem And Edmentioning
confidence: 97%
“…The relative vacancy formation energies in Zr 2 AlC are different from Cr 2 AlC and can be summarized as follows:Other MAX phases such as Ti 3 AlC 2 and Ti 3 SiC 2 exhibit a trend in vacancy formation similar to Zr 2 AlC 13, 31 . However, the results clearly depend on the synthesis conditions, as shown in the SI (Figures S3–S6).…”
Section: Resultsmentioning
confidence: 99%
“…During radiation damage the produced point defects may either recombine or reside on alternative lattice site forming antisite defects [61]. From a physical viewpoint a low energy antisite formation energy means that a high proportion of residual defects will remain in the material as typically the conversion of an interstitial into an antisite will result to a net reduction of defect mobility [61]. The antisite formation mechanisms are:…”
Section: Antisite Defect Formationmentioning
confidence: 99%
“…The radiation performance of materials is dependent upon their propensity to form and accommodate point defects [60,61]. A high concentration of defects may lead to the destabilization of the MAX phase (or any material) and may result to volume changes and microcracking [61][62][63].…”
Section: Implications Of Defect Processesmentioning
confidence: 99%
See 1 more Smart Citation